Formation and Oxidation Behaviour of Superalloy TMS-82+ Coated With a ?-Phase Re-based Alloy Diffusion Barrier Coatings - Thosin, Kemas; Lang, Fengqun; Narita, Toshio (Teknologi Indonesia, 2012)
A novel coating with duplex Re(W)-Cr-Ni and Ni(Cr)Al layers was formed on a nickel-base single-crystal superalloy TMS-82+, by electroplating Re(Ni), Ni(W) and Ni fi lms, followed by Cr-pack and then Al-pack cementations.A continuous Re-Cr-W-Ni ?-phase diffusion barrier was obtained after Cr-pack cementation. Addition of W to the Re-Cr-Ni ? phase decreased the Cr content, resulting in a ? phase with high melting temperature. The as-prepared Al reservoir layer has a duplex, Ni2Al3 and ?-Ni(Cr)Al layer, and during oxidation at 1423K, the Al reservoir layer changed into a ? phase containing (10-13) at %Al for the 1 hr-Al packed coating and into a mixture of ?- Ni(Cr)3Al and ?- Ni(Cr)Al phases for the 5hr-Al packed coating. A protective ?-Al2O3 scale formed during oxidation at 1423K in air, with the parabolic rate constant 7.410-11kg2m-4s-1 for the 1hr-Al packed coating and 6.610-10kg2m-4s-1 for the 5hr-Al packed coating. There was little diffusion through the ? layer during oxidation at 1423K for up to 100 hrs, without changing micro-structure of the TMS-82+ alloy.